2005
DOI: 10.1016/j.jbiomech.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced hardening of endothelial nucleus as an intracellular stress-bearing organelle

Abstract: The mechanical contribution of nucleus in adherent cells to bearing intracellular stresses remains unclear. In this paper, the effects of fluid shear stress on morphology and elastic properties of endothelial nuclei were investigated. The morphological observation suggested that the nuclei in the cytoplasm were being vertically compressed under static conditions, whereas they were elongated and more compressed with a fluid shear stress of 2 Pa (20 dyn/cm 2 ) onto the cell. The elongated nuclei remained the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 20 publications
10
104
0
Order By: Relevance
“…We demonstrated that this nuclear stiffening occurs in response to cell elongation due to a significant loss of nuclear volume, which induces chromatin condensation and dramatically affects cell proliferation. Our results give a physical insight in the stiffening of EC nuclei 41 and are consistent with previous works indicating that an important part of the nuclear volume (~45%) of isotropic ECs remains virtually free of DNA 42 , and that nuclear pores expand and transport rates increase when cells physically elongate 43 . As the typical timescale of stress fibre assembly (from several minutes to few hours) is larger than the characteristic plastic time of the nucleus (τ p~1 0 s) 40 , our model is also consistent with the current rheological view of the nucleus, which considers that the nucleus is stiff and resists distortions at short times, but it softens and deforms more readily at longer times 40,44 .…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that this nuclear stiffening occurs in response to cell elongation due to a significant loss of nuclear volume, which induces chromatin condensation and dramatically affects cell proliferation. Our results give a physical insight in the stiffening of EC nuclei 41 and are consistent with previous works indicating that an important part of the nuclear volume (~45%) of isotropic ECs remains virtually free of DNA 42 , and that nuclear pores expand and transport rates increase when cells physically elongate 43 . As the typical timescale of stress fibre assembly (from several minutes to few hours) is larger than the characteristic plastic time of the nucleus (τ p~1 0 s) 40 , our model is also consistent with the current rheological view of the nucleus, which considers that the nucleus is stiff and resists distortions at short times, but it softens and deforms more readily at longer times 40,44 .…”
Section: Discussionsupporting
confidence: 92%
“…Simulations suggest that complete aspiration of the nucleus into the micropipette occurs only for very low nucleus shear modulus values (Gnucl<0.1 kPa). Simulating isolated nuclei, Vaziri et al [39] also computes a low shear modulus based on experimental data for isolated endothelial cell nuclei [40] and isolated chondrocyte nuclei [7]. However, it should be noted that nucleus mechanical behaviour may be altered by the isolation technique used.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that as a result of turbulent blood flow in the retinal vein at A/V crossing induces endothelial damage and causes thrombus formation and venous occlusion [26][27][28] . Endothelium has important roles in regulating the response of hemodynamic changes and modification of cell shape [29][30][31][32] .…”
Section: Degenerative Changes Of the Vessel Wallmentioning
confidence: 99%